(3eLehYI aj GdgfOSIs - (3GQTejOSs
(3ChdgG (B:s
(3bGd GdCSJGP GdeNJU gPg ebGdI efShHI Edi CQTejOS ajgG CTcGd cKjQI GdahGFO ai CUhd GdgfOSI ai ZGjI GdLhOI s
(3BNQgG (B:s
(3hbO JHjf Pdc ai GdTcd GdKGdK YTQ ef GdebGdI GdKGdKI ef GdCUhd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3HgG CTcGd gfOSjIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1455s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs